Mozambique Jobs Diagnostic Volume 1. Analytics - Lachler, Ulrich (The World Bank, 2018)
This report focuses on the challenge of Mozambique's jobs transition: how to accelerate the shift into higher value-added activities and better livelihoods. As Mozambique enters the next phase of the demographic transition, the working-age population (WAP) is growing rapidly. Education levels are also steadily improving. However, good jobs are not expanding fast enough to absorb the growing, better educated labor force. The risk is that many young people will end up doing the same jobs as their parents-and in similar levels of poverty. In this context, the challenge is to help the labor force (particularly young people entering the labor market) increase their earnings by creating opportunities for more productive work. Regardless of whether they are engaged in self-employment or in wage jobs, it is necessary to link them to sources of capital, technology and markets, and to give them access to scale and agglomeration economies. Otherwise, the demographic dividend will be squandered